Depresión y su afectación en el estado emocional de una persona de 23 años de la ciudad de Guayaquil - Muñoz Gavilanez, Sheila Valeria (2022)
Depression is a disease that causes a feeling of constant sadness, discouragement, lack of energy, lack or increased appetite, physical and mental fatigue, sleep disturbances such as insomnia, makes it impossible for the individual to carry out their daily activities, other symptoms may also appear, such as pessimism about the future, feelings of guilt and inadequacy, ideas of suicide or death, for a diagnosis of depression the symptoms must usually last for two weeks or a month. The objective of this case study is to identify the consequences of depression on the emotional state of a twenty-three-year-old girl from the city of Guayaquil, the qualitative methodology used in this work is aimed at determining variables such as: Depression and emotional state which are exposed in the present case study, the symptoms and signs of the problem were evaluated through psychological instruments where symptomatology could be found, such as sadness, negative emotions, insomnia, deterioration of their self-esteem, feeling of guilt and disability due to the problems that are causing him, but through cognitive behavioral therapy his symptoms can be reduced and his quality of life improved. In order to do this, the proposal of a psychotherapeutic plan is proposed, which is oriented under cognitive behavioral techniques, developed for the therapeutic intervention of the patient, aimed at modifying those negative thoughts, feelings and behaviors that the patient manifested during the psychological intervention.